Growth mechanism of double cone-shaped nano zinc oxide prepared from zinc oxidation flue dusts by acid leaching. Issue 1 (11th June 2022) - Zhan, Feng; Yang, Lijiao; Guo, Xiaowei; Wang, Chunxia; Chen, Nanchun; Xie, Qinglin
Abstract: Cone-shaped nano zinc oxide was prepared by acid leaching-alkali precipitation using zinc oxidation flue dusts as raw materials. The dynamic conditions of acid leaching and the growth mechanism of ZnO crystal were also discussed. It was shown that the optimum acid leaching conditions were H2 SO4 concentration 2 mol/L, liquid–solid ratio 20:1, reaction time 4 h, reaction temperature 90 °C and Zn leaching rate was 94.98%. Then, the nano ZnO was prepared by acid leaching solution in an open hydrothermal system at low temperature. The formation process of nano ZnO crystals undergoes crystallization-dissolution-recrystallization under low temperature and alkaline conditions. Double cone-shaped ZnO nanoparticles could be obtained at 62 °C with n(Zn 2+ )/n(OH − ) ratio of 1:5 and reaction time of 1 h. The average size of ZnO nanoparticles was about 100 nm.